2009
DOI: 10.2165/11313860-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Clinical Variables in Comparative Analyses Using Propensity-Score Matching

Abstract: Addition of baseline Hb level as a variable in propensity score and ESA cost models affects ESA treatment cost estimates in patients with cancer receiving chemotherapy. Cost comparisons based on observational data should use analytical methods that account for differences in clinical variables between treatment groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
4

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 19 publications
0
5
0
4
Order By: Relevance
“…For example, Polsky et al found that medical claims were not sufficient for estimating the effect of treatments for chemotherapy-induced anaemia; clinical measures such as baseline haemoglobin greatly enhanced the ability to obtain accurate effect estimates. 28 Another challenge with administrative data in particular is that it will typically only include final paid claims, which may not fully reflect the care actually provided; or in the case of our pharmacy claims, a filled and paid for prescription does not verify that the patient actually used the medication as instructed. See Hersh et al for a discussion of these challenges in electronic health data.…”
Section: Complications When Using Electronic Health Datamentioning
confidence: 99%
“…For example, Polsky et al found that medical claims were not sufficient for estimating the effect of treatments for chemotherapy-induced anaemia; clinical measures such as baseline haemoglobin greatly enhanced the ability to obtain accurate effect estimates. 28 Another challenge with administrative data in particular is that it will typically only include final paid claims, which may not fully reflect the care actually provided; or in the case of our pharmacy claims, a filled and paid for prescription does not verify that the patient actually used the medication as instructed. See Hersh et al for a discussion of these challenges in electronic health data.…”
Section: Complications When Using Electronic Health Datamentioning
confidence: 99%
“…Note: Includes patients with Stage X, no stage data and unknown stage; Patients were assigned to the first, initial recorded stage in the instance that the patient had multiple stages in either GCS or GCCR; Patients may have had more than 1 primary tumor and were conunted in all multiple primary tumor types but only once in the total; Laterality was not used to determine stage values. The value of integrating multiple types of data to increase the completeness of information and provide cross-validation has been increasingly recognized as evidenced by a number of public and private initiatives, and demonstrated in several studies [4,[13][14][15][16][17]. Recently, the American Society of Clinical Oncology (ASCO) initiated…”
Section: Discussionmentioning
confidence: 99%
“…As an illustration of the value of more complete information in the area of oncology, a study by Polsky et al 2009 assessed the likely outcome in a claims-based only analyses of erythropoietin stimulating agents (ESA) costs by conducting propensityscore matching with and without baseline hemoglobin (Hb), which are recorded in electronic medical records (EMRs) [13]. The study found that claims-only studies could produce biased cost estimates and that adding data from an EMR, (e.g., Hb), materially altered the results.…”
Section: Unknown or Stage X Pre Vs Post Gcs/gccr Integration Unique mentioning
confidence: 99%
“…En consonancia con las directrices de los estudios de bases de datos retrospectivos de ISPOR [33], Polsky y cols. [34] analizaron la importancia de varios métodos de análisis (como el índice de propensión) para controlar el sesgo de selección de los pacientes cuando se comparan los costes del paciente a nivel individual. El análisis realizado por Polsky y cols.…”
Section: Discussionunclassified